20 Optic Flow Stimuli Effects on Standing Balance in Young and Older People with Low and High Fall Risk. (20th December 2019) - Sturnieks, Daina; Tan, Brandon; Persiani, Michela; Brodie, Matthew; Lord, Stephen
Abstract: Introduction: Optic flow stimuli can destabilise postural control, especially those with increased visual field dependence. This study aimed to examine the effects of optic flow stimuli on postural stability between: 1) younger and older adults; and 2) low-falls-risk and high-falls-risk older adults. Methods: 76 participants were grouped into 'young' (20-40 years, n=25), and 'old' (≥65 years, n=51); the latter was further stratified into 'old-LFR' (low fall risk, n=27) and 'old-HFR' (high fall risk, n=24). Participants stood on a force platform in a dark room with motion capture markers on the head, torso and lower limb. Optic flow stimuli were projected on a large screen encompassing the field of view as moving white dots for 30 seconds in four different conditions: radial expansion, radial contraction, circular (roll vection) anticlockwise and circular clockwise. Postural control was calculated from center of pressure (COP) and lower limb joint and trunk angles; changes between baseline (static dots) and optic flow conditions were compared between groups. Results: Optic flow stimuli led young and older participants to shift their COP in the expected direction for each stimulus condition (forward for expansion, backward for contraction, left for anticlockwise, right for clockwise). For radial expansion, significantly increased anteroposterior sway was found in old-LFR and old-HFR (p≤0.001) but not (p≥0.17). Similar results were seen for radial contraction. For circular clockwise, significantly increase mediolateral sway was found in old-HFR (p=0.002) but not young (p=0.912) or old-LFR (p=0.749). Results differed for circular anticlockwise, with greater changes seen in anteroposterior sway compared with mediolateral, particularly in old-HFR. No stimuli by group interaction effects were seen in body kinematics. Conclusions: Optic flow stimuli have a more destabilising effect on balance in older than younger adults, particularly those at increased risk of falling.